Motivasi Kerja Pegawai di Kantor Camat Sumalata Kabupaten Gorontalo Utara - Stevi H Mangolo; Rusdin Djibu; Widya Kurniati Mohi (Universitas Muhammadiyah Gorontalo, 2016)
This research is conducted in Sumalata Subdistrict Office, North Gorontalo district. The aim is at investigating and gaining the objective description of working motivation of the employee. It describes less strict attitude of the head of office towards the employee in accomplishing assignments, less incentive giving, less reward giving, and punishment related to the way they accomplish the assignments.This research shows that working motivation of the employee is still lack and has to be improved. It is suggested that the facilities in the office have to be enriched. It is necessary for the head of office to have strict personality and the discipline need to be developed. Moreover, giving incentive and rewards must be taken for granted to improve the employee motivation in working. Penelitian ini dilaksanakan di Kantor Camat Sumalata Kabupaten Gorontalo Utara.Tujuan dari penelitian ini adalah untuk mengetahui dan memperoleh gambaran yang objektif tentang motivasi kerja pegawai di Kantor Camat Sumalata Kabupaten Gorontalo Utara. Suatu penilitian yang menggabarkan kurang sikap tegas pimpinan kepada pegawai dalam penyelesaian pekerjaan, kurangnya pemberian bonus (Intensif) , Penghargaan (reward) , dan sanksi (punishment) terkait penyelesaian tugas-tugas kantor. Hasil penelitian menunjukan bahwa Motivasi kerja pegawai di Kantor Camat Sumalata masih kurang dan harus lebih ditingkatakan lagi. Peneliti menyarankan perlunya melengkapi sarana dan prasarana kantor, pentingnya sikap tegas dari pimpinan, peningkatan kedisiplinan dari pegawai, serta pemberian bonus dan penghargaan terhadap pegawai sehingga Motivasi Kerja Pegawai di Kantor Camat Sumalata Kabupaten Gorontalo Utara bisa maksimal.